2010
DOI: 10.1890/09-0766.1
|View full text |Cite
|
Sign up to set email alerts
|

Working less to gain more: when breeding quality relates to foraging efficiency

Abstract: In animal populations, a minority of individuals consistently achieves the highest breeding success and therefore contributes the most recruits to future generations. On average, foraging performance is important in determining breeding success at the population level, but evidence is scarce to show that more successful breeders (better breeders) forage differently than less successful ones (poorer breeders). To test this hypothesis, we used a 10-year, three-colony, individual-based longitudinal data set on br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
135
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(148 citation statements)
references
References 58 publications
12
135
0
1
Order By: Relevance
“…Our research on the foraging of Adélie penguins from Ross Island, using tags that identify geographic position and diving activity (e.g. Lescroël et al 2010, 2014, Ford et al 2014, provides evidence supporting predator-driven tropho-dynamics -facilitated by extensive diet overlap among penguins and cetaceans (Ainley et al 2006, Ballard et al 2012) -though they likely forage differently (see Discussion). By investigating phytoplankton biomass and penguin prey abundance where penguins do and do not forage, we might better understand the spatial and temporal components of the trophic interactions that occur within the pelagic food web.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Our research on the foraging of Adélie penguins from Ross Island, using tags that identify geographic position and diving activity (e.g. Lescroël et al 2010, 2014, Ford et al 2014, provides evidence supporting predator-driven tropho-dynamics -facilitated by extensive diet overlap among penguins and cetaceans (Ainley et al 2006, Ballard et al 2012) -though they likely forage differently (see Discussion). By investigating phytoplankton biomass and penguin prey abundance where penguins do and do not forage, we might better understand the spatial and temporal components of the trophic interactions that occur within the pelagic food web.…”
Section: Introductionmentioning
confidence: 71%
“…Diving data were processed using the program Divesum (v.7.5.5; G. Ballard unpublished software). Divesum classified dives into 3 types: foraging, exploratory, and other by parameterizing several components of each dive (Chappell et al 1993, Schreer et al 2001, Lescroël et al 2010, Ford et al 2014: (1) dive duration (s); (2) maximum depth (m); (3) depth change rate (m s −1 ; calculated as a running average for each 5 s block of the dive duration) in 2 categories: slow, i.e. < 1 m s −1 , or fast, i.e.…”
Section: Investigation Of Adélie Penguin Foraging/chick Provisioningmentioning
confidence: 99%
“…In addition, the best predictive models rely on large amounts of high quality demographic data, and sophisticated quantitative approaches. Yet, generating general predictions is difficult because of the inherent ecological variability amongst species, ecosystems (Chambers et al, 2011) and even among individuals (Lescroël et al, 2009(Lescroël et al, , 2010Lescroel et al, 2014) and populations (Tavecchia et al, 2008;Dias et al, 2010). These predictions, if they are local, can also be biased by dispersal processes (e.g., Woehler et al, 2014), because seabirds are very vagile, even species considered as highly philopatric .…”
Section: Predicting the Future Impacts Of Climate On Seabirdsmentioning
confidence: 99%
“…For example, Lescroël et al (2010) showed recently that in Adélie penguin populations, better breeders were also more efficient foragers than poorer breeders, especially when conditions were challenging. Given that we found a relationship between diet diversity and foraging success, it may be expected that more specialized individuals are also better breeders, particularly those individuals specialized on the most profitable prey in terms of biomass uptake (i.e.…”
Section: Discussionmentioning
confidence: 99%